KWL Strategy in Students’ Reading Comprehension of Descriptive Text - Sutadi, Riza Nurcahyani; Maharani, Mega Mulianing; Anwar, Choiril; Widiyati, Elok (Universitas Islam Sultan Agung, 2023)
This study focused on the KWL (Know-Want-Learned) strategy in students’ reading comprehension of descriptive text. The objective of this study was to find out how the KWL strategy could improve students’ reading comprehension of descriptive text. The design of the research was collaborative classroom action research. This research was conducted in two cycles; each cycle consisted of planning, action, observation, and reflection. By using the purposive sampling technique, the students in XD of a certain school in Semarang were selected as the sample of this study. The sample consisted of 30 students, 20 females and 10 males. The researchers used an observation sheet and a test to collect the data. The result showed that the KWL strategy was a way of teaching reading comprehension of descriptive text. Based on the test score, in cycle one, there were 50% students who achieved a minimum standard score, and in cycle two, 90% students achieved a minimum standard score. Thus, it could be concluded that the KWL strategy could improve students’ reading comprehension of descriptive text in the way of helping students to reach the minimum standard score.